1995
DOI: 10.1177/036354659502300307
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Joint Disease in Female Ballet Dancers

Abstract: The relationship between long-term ballet dancing and eventual arthrosis of the hip, ankle, subtalar, and first metatarsophalangeal joint was examined in 19 former professional female dancers, aged 50 to 70 years. The dancers were compared with pair-matched controls. All 38 women underwent medical history taking, clinical examination, and roentgenography of the joints studied. The roentgenographs were independently judged by two investigators and grouped according to a modified classification of Hermodsson. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
108
1
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(117 citation statements)
references
References 14 publications
3
108
1
3
Order By: Relevance
“…8,14,15 In general, osteophytes are a secondary manifestation of osteoarthritis, [15][16][17] but in the ankle repetitive minor trauma can induce the formation of the spur commonly seen in soccer players and ballet dancers. 15,[18][19][20] It has been suggested that this is caused by excessive strain on the anterior joint capsule or by repetitive trauma. 15,19,21 In our study, 18 of the 22 ankles showing tibial and talar osteophytes had them located within the joint capsule and not at the site of attachment of the capsule; hence they could not be due to capsular strain.…”
Section: Discussionmentioning
confidence: 99%
“…8,14,15 In general, osteophytes are a secondary manifestation of osteoarthritis, [15][16][17] but in the ankle repetitive minor trauma can induce the formation of the spur commonly seen in soccer players and ballet dancers. 15,[18][19][20] It has been suggested that this is caused by excessive strain on the anterior joint capsule or by repetitive trauma. 15,19,21 In our study, 18 of the 22 ankles showing tibial and talar osteophytes had them located within the joint capsule and not at the site of attachment of the capsule; hence they could not be due to capsular strain.…”
Section: Discussionmentioning
confidence: 99%
“…was consulted to achieve a final judgement. Radiographic osteoarthritis (ROA) of the tibiotalar joint was quantified by the grading scale of Van Dijk et al [14] into four grades (range 0-3) (see Appendix).…”
Section: Radiographic Examinationmentioning
confidence: 99%
“…Ancak mesleki olarak balerin ve futbolcularda daha sık os trigonum sendromu görüldüğü raporlanmıştır (12,13). En pointe hareketini yapan 19 balerin ve balet ile yapılan bir çalışmada, hiçbir hastada arka ayak ağrısı semptomu bulunmazken 38 ayak bileğinin 18'inde radyolojik olarak os trigonum varlığı görülmüştür (14). Ancak olgumuzun bu iki meslek grubuyla ilişkisi olmadığı gözlenmiştir.…”
Section: Discussionunclassified